Kecemasan Matematika Siswa dalam Pembelajaran - Siti Ashari Arbiah Harahap; Vebi Radiatul Rahman (Griya Journal of Mathematics Education and Application, 2023)
Mathematical packaging is an uncomfortable condition such as feeling worried, tense, and so on when facing math problems. This paper aims to describe math anxiety, types of anxiety, factors of math anxiety and efforts to overcome them. The method used in this research is the literature study method. The approach used is a literature study approach with sources derived from articles and papers. From the sources obtained, then the most relevant data is selected. Based on several research sources, it can be seen that anxiety has a negative impact on learning success. The factors that cause mathematics anxiety are factors from within and outside the student's self. Factors from within students such as personality factors (psychological or emotional) and intellectual factors (cognitive). Meanwhile, external factors such as environmental (social) factors. Thus the treatment that can be given is to convince themselves to be able to solve math problems, parents are expected not to stress their children to get good grades in mathematics, and teachers are expected to provide a gradual and clear understanding. Kecemasan matematika adalah kondisi yang tidak nyaman seperti perasaan khawatir, tegang, dan sebagainya ketika menghadapi permasalahan matematikaTulisan ini bertujuan untuk mendeskripsikan kecemasan matematika, jenis-jenis kecemasan, faktor-faktor kecemasan matematika dan upaya mengatasinya. Metode yang digunakan dalam penelitian ini adalah metode studi pustaka. Pendekatan yang dipakai adalah pendekatan studi literatur dengan sumber yang berasal dari artikel dan makalah. Dari sumber yang didapatkan, kemudian dipilih data yang paling relevan. Berdasarkan beberapa sumber penelitian, dapat diketahui bahwa kecemasan berdampak buruk terhadap keberhasilan belajar.Faktor yang menyebabkan terjadinya kecemasan matematika yaitu faktor dari dalam dan luar diri siswa. Faktor dari dalam diri siswa seperti faktor kepribadian (psikologis atau emosional) dan faktor intelektual (kognitif). Sedangkan faktor dari luar siswa seperti faktor lingkungan (sosial). Dengan demikian penanganan yang dapat diberikan adalah menyakinkan dirinya mampu menyelesaikan permasalahan matematika, orangtua diharapkan tidak menekankan anaknya untuk mendapatkan nilai yang bagus dalam pelajaran matematika, dan guru diharapkan memberikan pemahaman secara bertahap dan jelas.